Groundwater Abstraction has Caused Extensive Ecological Damage to the Doñana World Heritage Site, Spain - Green, Andy J.; Guardiola-Albert, Carolina; Bravo-Utrera, Miguel Ángel; Bustamante, Javier; Camacho, Antonio; Camacho, Carlos; Contreras-Arribas, Eva; Espinar, José L.; Gil-Gil, Teresa; Gomez-Mestre, Iván; Heredia-Díaz, Javier; Kohfahl, Claus; et al. (Wetlands (Wilmington, N.C.), 2024)
Acreman et al. (Wetlands 42:63, 2022 ) reviewed evidence for ecological damage to the Doñana wetlands (UNESCO World Heritage Site [WHS] and Ramsar site), Spain, associated with intensification of groundwater use, particularly for agriculture. Acreman et al. presented a multistep methodology for evidence-based risk assessment that involves identification of conservation issues, and a systematic review of scientific evidence for ecological damage and its causes. However, they involved few local scientists, used a questionable methodology in stakeholder selection and involvement, used a flawed conceptual framework, and an incomplete literature review. We propose improvements to their methodology. They overlooked or misinterpreted key evidence, and underestimated the impacts that abstraction for irrigation for red fruits (mainly strawberries), rice and other crops has had on Doñana and its biodiversity. They reported groundwater level depletion of up to 10 m in the deep aquifer, but wrongly concluded that there is no evidence for impacts on the natural marsh ecosystem, the dune ponds or the ecotone. Groundwater drawdowns are actually up to 20 m, and have inverted the formerly ascending vertical hydraulic gradient in discharge areas. Phreatic levels have been lowered from 0.5 to 2 m in some areas. Groundwater abstraction has caused multiple ecological impacts to temporary ponds and marshes in the WHS, as well as to terrestrial vegetation, and should be urgently reduced. Furthermore, Acreman et al. focused on groundwater quantity while overlooking the importance of severe impacts on quality of both surface and groundwater, intimately connected to the use of agrochemicals for irrigated crops.